(untitled) (Research, Society and Development, 2021)
Landslides have been the object of extensive studies in the world, not only for their importance as active agents of modifications of relief forms, but also because can damages and losses to people and exposed structures, affecting various kinds of enterprises. This study had as objective the determination of influencing parameters on the development of landslides in the slopes aside of Estrada de Ferro Vitória-Minas (EFVM). EFVM is located in the southeastern region in Brazil and is an important railroad for the transportation of iron ore to the steel mills and for exportation, as well as for passenger transportation. The database used herein was collected from field work in EFVM, together with image processing and data in laboratory tests. The parameters selected to be evaluated were Atterberg limits, cohesion, friction angle, permeability and classification of soil in the slopes. Estimates were done on the volumes and areas of landslides that have already occurred in the slopes. Among the studied parameters, the results obtained for the Atteberg limits and soil cohesion were the most relevantly correlated with the field results, which is in accordance with other studies from literature. It is concluded that Atterberg limits are directly related to soil ruptures, and soil cohesion contributes to soil stabilization in slopes.